ANATOMICAL CHANGES OF KEKABU WOOD (Bombax ceiba L.) DUE TO MECHANICAL DENSIFICATION - Krisdianto, Krisdianto; Balfas, Jamal (Secretariat of Forestry Research and Development Agency, 2005)
Kekabu wood (Bombax ceiba L.), which is locally known as kapok or randu has long been planted as crops troughout the country, as fiber producer aimed for stuffing pillow. This species is considered as a giant tree which could produce a large quantity of timber. Unfortunately, the timber is too soft, having low density and several physical defects during drying, limiting its uses in conventional wood processing. Any treatment which could significantly increase its structural density may be useful for diversifying the uses of this timber. This study examined some anatomical changes that may exist during mechanical densification. Wood samples measuring 40 mm thick, 40 mm wide and 500 mm long were steamed at 126°C for 30 minutes prior to pressing of 23.75 kg/cm. Anatomical measures were undertaken using light microscope and scanning electron microscope on both treated and untreated samples. Results showed that the treatment significantly reduced void volume and ray distance of approximately a half the initial wood structure, followed by an increased in wood density of more than 50%.